Etat Des Lieux Du Dispositif D’alimentation Dans Quelques Écoles Primaires De La Ville De Yaoundé (Cameroun) - Annie-Claude Pial; Malika Mboupaing; Majesté Mbiada Pahane; Germain Ndengue (European Scientific Journal, ESJ, 2017)
School feeding refers to all the conditions through which pupils have access, choose and consume food within the school. School feeding has gained increasing attention in recent years and it is an important route in the process for achieving quality education. The availability of healthy and balanced food in schools is a necessity highlighted in many studies. In developed countries, the institutional framework for school feeding is well developed, schools have canteens, where the meals are prepared and consumed by children according to health standards. The situation is different in developing countries, especially in Cameroon where we carried out a study with an aim to have an overview of the feeding organization in some primary schools in the Yaounde I subdivision. The methodology adopted consist of a survey carried out amongst school stakeholders (school principals, teachers, students and food handlers) and visits to targeted schools. According to the results obtained, 85% of the targeted schools don’t have a building space, equipped with all the amenities (Clean water, tables, chairs, toilets) and ready to receive food vendors. Different types of foods are served to children (meals, pastries, fruits, sweets, beverages and icecreams). Unfortunately, those foods are prepared and serve under low hygienic conditions according to standards required for this purpose. Many deficiencies have been highlighted in the framework of our study and in order to mitigate them, the national government should take some actions such as the development of a national policy, the establishment of an adequate institutional framework, the development of a sustainable financing strategy and a capacity building strategy food handlers.